Prevalence and Characteristics of Forward Head Posture among University Students - Lukman Faishal Fatharani; Rina Purnamasari; Mohammad Raihan Diki Ramadhan; Galih Prakasa Adhyatma (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Forward head posture (FHP) is a condition of misalignment in the cervical vertebrae where the cervical spine shifts towards a more anterior angle. This change induces stress on the surrounding anatomical structures, leading to comorbidities and pathology. FHP has been identified as prevalent among young adults. Various risk factors contribute to this demographic's high burden of FHP, including increased exposure to modern technologies, such as smartphones. Therefore, our study aims to investigate the prevalence of FHP among university students in our center and analysed risk factors associated with FHP. Methods: This cross-sectional study was conducted on students of Universitas Muhammadiyah Semarang. A total of 126 participants were enrolled. Diagnosis of FHP was determined by measuring the craniovertebral angle (CVA) using ImageJ. Data of risk factors was collected by questionnaire, smartphone addiction scale-short version (SAS-SV) and the neck pain disability index. Ethical approval was obtained from the ethics committee of Universitas Muhammadiyah Semarang and participants provided informed consent. Results: The prevalence of FHP in our center was 63.5%. The mean CVA was 48±6o. We discovered that overweight or obese participants had almost 4 times the odds of developing FHP (aOR=3.899, 95%CI [1.3;11.6], p=0.014). A similar trend was also observed in participants with smartphone addiction, who were 4.5 times more likely to develop FHP (aOR=4.41, 95%CI [1.76;11.04], p=0.002). We did not observe a significant association between FHP and neck pain. Conclusion: Our study demonstrates the considerable prevalence of FHP in our center, especially in those with higher BMI and addiction to smartphones. However, we advise caution in interpreting this study to a broader population of students due to its small sample size and cross-sectional design. We recommend larger longitudinal studies analysing strategic risk factors of FHP to construct a basis of policymaking for effective prevention and targeted intervention.